Persis (Anapersis) Fennah, 1952 (Hemiptera: Fulgoroidea: Derbidae) from Brazil and identification key to the New World species - Cantanhede, Inezita; Viegas, Eduarda Fernanda Gomes; Ale-Rocha, Rosaly (Zootaxa, 2025)
We report, for the first time, the occurrence of the subgenus Persis (Anapersis) in Brazil, based on the description of P. (Anapersis) takiyae sp. nov.. A key to the subgenera of Persis, as well as to six species of Persis (Anapersis) is provided.